COMPARATIVE ANALYSIS OF MARKETING AND LOGISTICS DEPARTMENTS - K. Igrokova (Вестник университета)
The arguments proving necessity of interaction of marketing and logistics departments in a company. The modern evaluation treatment connecting main comparative characteristics of marketing and logistics is given. The carrying out of evaluation content of logistics and marketing for the efficiency of their interaction. The marketing and logistics functional contects are discussed. These comparative characteristics are concretized towards all funtional directions. Communication management efficiency with competent interactions of services of marketing and logistics is tracked.